Donations Made and Received: A Study of Disclosure Practices of Pharmaceutical Companies and Patient Groups in Canada - Joel Lexchin (Kerman University of Medical Sciences, 2022)
Given the increasing role of patient groups in pharmaceutical policy-making in Canada, this observational study was undertaken to determine whether companies that are members of Innovative Medicines Canada (IMC) list, on their publicly available websites, the names of patient groups that they make donations to and reciprocally, whether patient groups publicly list the names of the companies that they receive donations from. Websites of IMC members were searched for the names of the patient groups receiving donations, value of the donations and year the donations were made. The website of each patient group that was listed as receiving a donation was then searched for information about the name of companies making donations along with the value of the donations, year the donations were made and percent of the patient groups' income represented by the donation. For donations over $50 000, an attempt was made to match donations that companies made to donations that patient groups received. Eleven of 44 IMC members reported making 165 donations to 114 different patient groups. Seventy-nine of these 114 groups reported receiving 373 donations from IMC members. Information about the value of donations, the year that they were given and received and the percent of patient groups' income that they represented was limited. Donations made and received could not be matched because of the absence of information about the donations. Reporting on websites about donations by both companies and patient groups in Canada is haphazard, inconsistent and incomplete. Reforms are need to both the way that companies and patient groups report donations.